Isolation, Characterization and Antibacterial Evaluation on Long Chain Fatty Acids From Limnophila polystachya Benth. - Kalimuthu, S.; Latha, S.; Selvamani, P.; Rajesh, P.; Balamurugan, B.; Chandrasekar, T.M. (Asian Journal of Chemistry, 2010)
Limnophila polystachya Benth. is a herb belongs to the family Scrophulariaceae; widely used in traditional Indian medicine for various debilitating diseases such as pestilent fever, dysentery, elephantiasis, dyspepsia and also exhibits significant antibacterial, antifungal and antineoplastic activities. Preliminary photochemical screening on this plant showed that the presence of alkaloids, flavonoids, glycosides, steroids, tannins and terpenoids. The ethanolic extract of Limnophila polystachya was subjected to thin layer and column chromatography using petroleum ether:ethyl acetate in the ratio of (3.75:1.25) as solvent system for the isolation of bioactive phytoconstituents obtained after fractional crystallization using silica gel (60-120) mesh. The colourless crystalline compounds further purified using chromatographic methods and elucidated with spectral techniques such as UV, IR, 1H NMR, 13C NMR, elemental analysis and LCMS. The amorphous crystalline compound was elucidated as CH3-(CH2)30-COOH (Do-triacontanoic acid, Syn: lacceroic acid). Antibacterial activity was assessed on isolated crystals against gram negative and positive bacterial pathogenic organism. The elucidated crystals showed that significant activity against the pathogenic organisms at the diameter 600 and 1000 μg/mL at significant zone of inhibition. Lacceroic acid has been exhibited antibacterial activity against different pathogenic organism.